Coated steel sheet and method for manufacturing same

By forming a film of organic resin and wax on the steel plate, the distribution of wax deficiency is controlled, and the friction coefficient is reduced, the cracks and mold wear problems in complex shape press forming are solved, and the press moldability and coating properties of the steel plate are improved.

CN119156280AActive Publication Date: 2024-12-17JFE STEEL CORP
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202380036501.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-07
Filing Date
2023-05-15
Publication Date
2024-12-17
Estimated Expiration
2043-05-15

AI Technical Summary

Technical Problem

The existing coated steel plates are prone to cracks and mold wear during the pressing and forming process of complex shapes, resulting in a decrease in productivity, and the prior art lubrication methods are costly or lead to deterioration of coating properties.

Method used

Using a film containing organic resin and wax, the area ratio and average area of ​​the wax-deficient part are controlled to significantly reduce the friction coefficient between the steel plate and the mold and improve lubricity.

Benefits of technology

It realizes crack-free molding and mold wear suppression in pressing complex shapes, improves the press moldability of steel plates, is suitable for molding complex shapes, and has good coating properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119156280A_ABST
    Figure CN119156280A_ABST
Patent Text Reader

Abstract

Provided is a coated steel sheet having excellent press moldability. The coated steel sheet is provided with a coating film containing a predetermined organic resin and wax, the area ratio of a wax-deficient portion of the coating film with respect to the entire coating film is 20.0% or less, the average area of the wax-deficient portion is 50.0 [mu] m2 or less, and the amount of adhesion to one surface of the coating film is 0.3 g / m2 or more.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a coated steel sheet, and more particularly to a coated steel sheet having excellent press formability. In addition, the present invention relates to a method for producing the coated steel sheet. Background Art

[0002] Steel sheets such as cold-rolled steel sheets and hot-rolled steel sheets are widely used in various fields. For example, in applications such as automobile bodies, steel sheets are generally press-formed before use. Therefore, the steel sheets are required to have excellent press-formability.

[0003] In recent years, in order to improve the design of the product, there is a tendency to press-form into a more complicated shape. In addition, in order to simplify the manufacturing process, in promoting the integration of parts, in this sense, there is also a tendency to press-form into a more complicated shape.

[0004] However, when a steel sheet is press-formed into a complex shape, the steel sheet may be unable to withstand the forming and may break, or die galling may occur during continuous press forming. This results in a serious adverse effect on the productivity of products such as automobiles. Therefore, there is a demand for further improvement in press formability.

[0005] As a method for improving press formability, for example, a method of surface treating the mold used in press forming can be cited. Although this is a widely used method, there is a problem that once the surface treatment is performed, the mold cannot be adjusted afterwards. In addition, there is also a problem of high cost.

[0006] As a method for improving press-forming properties without performing surface treatment on the mold, there is a method of using high-viscosity lubricating oil. However, since the press-formed parts obtained by this method are in a state where the high-viscosity lubricating oil adheres, degreasing may be poor after press-forming. If degreasing is poor, the paintability is deteriorated.

[0007] Therefore, it is required to improve the press formability of the steel sheet itself instead of surface treatment of the mold and high-viscosity lubricating oil.

[0008] As a technique for improving the press formability of a steel sheet itself, it has been proposed to perform a surface treatment to form a lubricating film on the surface of the steel sheet.

[0009] For example, Patent Document 1 proposes a coated steel sheet in which an acrylic resin coating is formed on the surface of a galvanized steel sheet.

[0010] Patent Document 2 proposes that, in a coated metal sheet having a resin film formed on the surface of the metal sheet, a solid lubricant is made to protrude from the surface of the resin film by 0.01 to 1.5 μm.

[0011] Patent Document 3 proposes coating the surface of a metal product with a film having a thickness of 0.5 to 5 μm containing a lubricant in a polyurethane resin.

[0012] Patent Document 4 proposes a coated steel sheet having an alkali-soluble organic coating obtained by adding a lubricant to an epoxy resin.

[0013] Prior art literature

[0014] Patent Literature

[0015] Patent Document 1: Japanese Patent Application Laid-Open No. 09-170059

[0016] Patent Document 2: Japanese Patent Application Laid-Open No. 10-052881

[0017] Patent Document 3: Japanese Patent Application Publication No. 2000-309747

[0018] Patent Document 4: Japanese Patent Application Publication No. 2000-167981 Summary of the invention

[0019] However, in the techniques proposed in Patent Documents 1 to 4, although the lubricity is improved to a certain extent due to the effect of the lubricant contained in the film, the formability in complex press molding is not sufficient. Specifically, there are the following problems: cracks are generated in crack-prone areas during press molding, or mold wear is generated in areas where the surface pressure increases.

[0020] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a coated steel sheet having excellent press formability.

[0021] The present inventors paid attention to a coated steel sheet having a coating film composed of an organic resin and a wax and conducted intensive studies to solve the above-mentioned problems. As a result, they obtained the following findings.

[0022] (1) When a steel sheet formed with a film containing an organic resin and wax is press-formed, the film is scraped off by the mold when the film surface and the mold surface slide, and the lubricating film formed by the mixture of organic resin and wax in the film covers the mold surface and the sliding surface of the steel sheet. Therefore, in order to improve press-formability, it is necessary to improve the sliding property of the lubricating film covering the sliding surface of the mold surface and the steel sheet, that is, to reduce the friction coefficient.

[0023] (2) By using a specific organic resin and wax and controlling the area ratio of the wax-deficient portion in the film and the average area of ​​the wax-deficient portion, the friction coefficient can be significantly reduced.

[0024] The present invention has been accomplished based on the above findings, and the gist of the present invention is as follows.

[0025] 1. A coated steel sheet comprising a base steel sheet and a coating film containing an organic resin and a wax provided on at least one surface of the base steel sheet, wherein:

[0026] The organic resin is at least one selected from styrene resin, epoxy resin, phenolic resin and polyester resin.

[0027] The wax is a polyolefin wax having a melting point of 100°C to 145°C and an average particle size of 3.0 μm or less.

[0028] In the film, the area ratio of the wax-deficient portion to the entire film is 20.0% or less, and the wax-deficient portion is defined as a region where the ratio of the mass of the wax to the mass of the organic resin is 1 / 10 or less,

[0029] The average area of ​​the wax-deficient part is 50.0 μm 2 the following,

[0030] The adhesion amount on one side of the above film is 0.3g / m 2 above.

[0031] 2. The coated steel sheet according to item 1 above, wherein the ratio of the organic resin in the coating is 30% by mass to 95% by mass,

[0032] The ratio of the wax in the film is 5% by mass to 50% by mass.

[0033] 3. The coated steel sheet according to 1 or 2 above, wherein the arithmetic mean roughness Ra of the surface of the base steel sheet is 0.4 μm to 2.5 μm.

[0034] 4. The coated steel sheet according to any one of 1 to 3 above, wherein the coating has an adhesion amount of 2.5 g / m 2 the following.

[0035] 5. The coated steel sheet according to any one of 1 to 4 above, wherein the organic resin is an alkali-soluble resin.

[0036] 6. The coated steel sheet according to any one of 1 to 5 above, wherein the coating further contains a rust inhibitor.

[0037] 7. The coated steel sheet according to item 6 above, wherein the rust inhibitor is at least one selected from the group consisting of aluminum salts, zinc salts and zinc oxide of phosphoric acid.

[0038] 8. The coated steel sheet according to any one of 1 to 7 above, wherein the coating further contains a dispersant.

[0039] 9. The coated steel sheet according to 8 above, wherein the dispersant is at least one selected from the group consisting of sodium polycarboxylate, sodium polyacrylate, carboxylic acid copolymer and sulfonic acid copolymer.

[0040] 10. The coated steel sheet according to any one of 1 to 9 above, wherein the coating further contains silicon dioxide.

[0041] 11. A method for producing a coated steel sheet, which is the method for producing a coated steel sheet according to any one of 1 to 10 above, comprising applying a coating material comprising an organic resin and a wax to at least one surface of a base steel sheet and drying the coating material, wherein:

[0042] The organic resin is at least one selected from styrene resin, epoxy resin, phenolic resin and polyester resin.

[0043] The wax is a polyolefin wax having a melting point of 100° C. to 145° C. and an average particle size of 3.0 μm or less.

[0044] 12. The method for producing a coated steel sheet according to 11 above, wherein the maximum reaching temperature of the base steel sheet during the drying is 60° C. to the melting point of the wax.

[0045] 13. The method for producing a coated steel sheet according to 11 or 12 above, wherein the ratio of the total solid content in the coating material is 1% by mass to 30% by mass.

[0046] According to the present invention, the friction coefficient between the steel plate and the die can be significantly reduced. As a result, according to the present invention, even for a portion that is prone to cracking during press forming, it is possible to form without cracking. In addition, according to the present invention, it is possible to suppress die wear at a portion with high surface pressure. Therefore, the coated steel plate of the present invention has extremely good press formability and can be well applied to forming into complex shapes. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] Figure 1 This is an example of a mapping image of the peak intensity ratio of the wax component to the organic resin component obtained by micro-Raman spectroscopy.

[0048] Figure 2 This is an example of a mapping image of the peak intensity ratio of the wax component to the organic resin component obtained by micro-Raman spectroscopy.

[0049] Figure 3 It means analysis Figure 1 A diagram showing the distribution of the wax-deficient portion obtained by using a mapping image.

[0050] Figure 4 It means analysis Figure 2 A diagram showing the distribution of the wax-deficient portion obtained by using a mapping image.

[0051] Figure 5 This is a schematic front view showing a friction coefficient measuring device.

[0052] Figure 6 Yes means Figure 5 A simplified three-dimensional diagram of the flange shape and size. DETAILED DESCRIPTION

[0053] Hereinafter, examples of embodiments of the present invention will be described. In the following description, unless otherwise specified, the unit "%" of content means "mass %".

[0054] (1) Coated steel plate

[0055] A coated steel sheet according to one embodiment of the present invention includes a base steel sheet and a coating provided on at least one surface of the base steel sheet.

[0056] [Membrane]

[0057] The film contains an organic resin and wax. Each component is described below.

[0058] (Organic resin)

[0059] In the present invention, the organic resin acts as a binder to hold the wax on the steel plate surface. Since the inorganic binder has a low affinity with polyolefin, it is not possible to obtain the effect of imparting sliding properties by forming a lubricating film. Therefore, it is important that the film contains an organic resin.

[0060] As the organic resin, at least one selected from styrene resins, epoxy resins, phenolic resins and polyester resins is used. As the organic resin, two or more kinds of resins may be mixed and used.

[0061] As the above-mentioned styrene resin, any styrene resin can be used without particular limitation. Here, the styrene resin refers to a polymer containing a styrene monomer as a constituent component, typically a homopolymer of styrene and a copolymer containing styrene. As the above-mentioned copolymer, for example, a copolymer of styrene with at least one selected from acrylic monomers, nitrile groups, ethylene and butadiene can be cited. The above-mentioned styrene resin is preferably a styrene acrylic resin. By copolymerizing acrylic acid and styrene, the compression moldability is further improved compared to the case where acrylic acid is not contained.

[0062] As the epoxy resin, any epoxy resin can be used without particular limitation. Examples of the epoxy resin include bisphenol A epoxy resin, bisphenol F epoxy resin, and novolac epoxy resin.

[0063] As the phenolic resin, any phenolic resin can be used without particular limitation. As the phenolic resin, a resol-based phenolic resin that is soluble or dispersible in an aqueous solvent is preferably used.

[0064] As the polyester resin, any polyester resin can be used without particular limitation. As the polyester resin, it is preferable to use a polyester resin containing a monomer having a carboxyl group as a constituent component.

[0065] From the viewpoint of film removability, the organic resin is preferably an alkali-soluble resin. That is, when the steel sheet is used for automobile bodies, etc., coating is performed after press forming. At this time, if the organic resin is an alkali-soluble resin, the film can be removed (film removal) in the alkali degreasing process performed before coating. Therefore, the subsequent coating can be performed well.

[0066] The above-mentioned film may contain an organic resin in any proportion. However, if the proportion of the organic resin is too low, the influence of components other than the organic resin becomes greater, and the effect of the organic resin is relatively reduced. Therefore, from the viewpoint of improving the effect of the organic resin, it is preferred that the proportion of the above-mentioned organic resin in the above-mentioned film is 30% or more. By making the proportion of the above-mentioned organic resin be 30% or more, the effect of improving the press moldability can be further improved, and the effects of the organic resin such as demolding properties and adhesion can be fully exerted. The proportion of the above-mentioned organic resin in the above-mentioned film is more preferably 40% or more, and further preferably 50% or more. On the other hand, there is no particular upper limit to the proportion of the above-mentioned organic resin, but in order to add a certain amount of wax as described later, it is preferably 95% or less, and more preferably 90% or less.

[0067] Here, the ratio of the organic resin in the film is defined as the ratio of the mass of the solid content of the organic resin in the film to the total mass of the total solid content in the film.

[0068] The mass average molecular weight of the organic resin is not particularly limited. However, if the mass average molecular weight is less than 5000, the rust resistance is poor sometimes. Therefore, from the viewpoint of rust resistance, the mass average molecular weight of the organic resin is preferably 5000 or more, more preferably 7000 or more, and further preferably 9000 or more. On the other hand, if the mass average molecular weight of the organic resin exceeds 30000, the adhesion is sometimes deteriorated. Therefore, from the viewpoint of adhesion, the mass average molecular weight of the organic resin is preferably 30000 or less, more preferably 25000 or less, and further preferably 20000 or less.

[0069] Here, the mass average molecular weight of the organic resin is a mass average molecular weight measured in accordance with JIS K 7252 "Plastics - Method for determining average molecular weight and molecular weight distribution of polymers by size exclusion chromatography".

[0070] (wax)

[0071] As the wax, polyolefin wax is used. Polyolefin wax has low surface energy and self-lubricating property. Therefore, by providing a film containing polyolefin wax on the surface of the base steel plate, excellent press formability can be obtained. In addition, polyolefin can be relatively easily adjusted to the melting point within the range described below by controlling the density and molecular weight. Among polyolefin waxes, polyethylene wax is preferably used because the best lubricating effect can be obtained when polyethylene wax is used.

[0072] Melting point: 100~145℃

[0073] The melting point of the polyolefin wax is 100°C to 145°C. As mentioned above, the polyolefin wax itself has self-lubricating properties. In addition, if the melting point of the polyolefin wax is within the above range, the polyolefin wax becomes semi-molten due to the frictional heat generated by the sliding of the mold during press molding, and the lubricating film formed by the mixture of organic resin and wax covers the mold surface and the sliding surface of the steel plate. As a result, the direct contact between the mold and the steel plate is suppressed, so the press moldability is significantly improved.

[0074] If the melting point of the polyolefin wax is less than 100°C, the polyolefin wax completely melts due to the frictional heat generated by sliding during press molding, so the lubricating effect of the polyolefin wax cannot be fully exerted, and the coating effect of the above-mentioned mold cannot be obtained. Therefore, the melting point of the polyolefin wax is above 100°C, preferably above 120°C. On the other hand, if the melting point of the polyolefin wax is higher than 145°C, the polyolefin wax does not melt due to the frictional heat during press molding, so not only can a sufficient lubricating effect not be obtained, but also the coating effect of the mold cannot be obtained. Therefore, the melting point of the polyolefin wax is below 145°C, preferably below 140°C.

[0075] Here, the melting point of the polyolefin wax is defined as the melting temperature measured based on JIS K 7121 "Determination of Transition Temperatures of Plastics".

[0076] Average particle size: 3.0 μm or less

[0077] If the average particle size of the polyolefin wax is greater than 3.0 μm, the polyolefin wax is easily condensed in the film, and the wax-deficient portion cannot meet the conditions described later. In addition, during the sliding of the mold during compression molding, the organic resin and the wax become difficult to mix, and the coating effect of the above-mentioned mold cannot be obtained, and excellent compression molding cannot be obtained. Therefore, the average particle size of the above-mentioned polyolefin wax is less than 3.0 μm, preferably less than 1.5 μm, more preferably less than 0.5 μm, and further preferably less than 0.3 μm. On the other hand, the lower limit of the average particle size of the polyolefin wax is not particularly limited, but if it is too small, sometimes the polyolefin wax is dissolved in the lubricating oil during compression molding, and the lubricity improvement effect is reduced. In addition, since the polyolefin wax is easily condensed in the coating, not only the coating stability becomes low, but also a coarse wax-deficient portion is easily formed. Therefore, the average particle size of the above-mentioned polyolefin wax is preferably more than 0.01 μm, more preferably more than 0.03 μm.

[0078] Here, the above average particle size can be measured by observing the wax particles on the film surface using a scanning electron microscope (SEM). That is, it is obtained by obtaining a SEM image set to a magnification corresponding to the wax particle size and performing image analysis. The average value of the equivalent circle diameter of each wax particle obtained by the above image analysis is used as the above average particle size.

[0079] Hereinafter, the method for measuring the average particle size of wax particles using SEM will be specifically described. When using SEM to measure the average particle size of wax particles, in order to suppress the diffusion and transmission of the electron beam and obtain information about the wax particles near the surface of the film, it is necessary to sufficiently reduce the acceleration voltage. For this reason, it is preferably measured at an acceleration voltage of less than 1 kV. In addition, in order to prevent image obstruction caused by charging during observation and clearly identify wax particles, it is preferred to implement a coating of conductive materials such as C, Au, and Os. The film thickness of the coating of the above-mentioned conductive material is preferably less than 2 nm. The measurement range of the SEM image must be able to identify wax particles and include a statistically significant number of wax particles. For example, when the diameter of the wax particles is 100 nm to 300 nm, it is preferred that the pixel size is less than 30 nm and the measurement range is more than 10 μm × 10 μm. It should be noted that the SEM image can be obtained by measuring multiple fields of view continuously or arbitrarily, and multiple SEM images are obtained in a manner that satisfies the above-mentioned measurement range in total.

[0080] The film may contain wax in any proportion. However, if the proportion of wax in the film is too high, the proportion of the organic resin as a binder is relatively reduced, and the wax component is easy to fall off. In addition, the adhesion is reduced. In addition, when painting is carried out, the film is not fully removed from the surface of the steel plate in the alkali degreasing process, and sufficient degreasing cannot be obtained, resulting in deterioration of the coating properties. Therefore, the proportion of wax in the film is preferably 50% or less, and more preferably 30% or less.

[0081] On the other hand, the lower limit of the ratio of the above-mentioned wax is not particularly limited. However, if the ratio of the wax is increased, there is a tendency that the area ratio and average area of ​​the wax-deficient portion described later are reduced and the press moldability is improved. Therefore, from the viewpoint of further improving the press moldability, it is preferred that the ratio of the wax in the above-mentioned film is 5% or more, more preferably 10% or more.

[0082] Here, the ratio of the wax in the film is defined as the ratio of the mass of the solid content of the wax in the film to the total mass of the total solid content in the film.

[0083] (Wax lacking part)

[0084] Wax deficiency area ratio: 20.0% or less

[0085] When a film containing an organic resin and wax is formed on the surface of the base steel plate, the wax tends to condense and be unevenly distributed in the film. As a result, an area (wax-deficient area) in which the proportion of wax is significantly low is formed in the film. Moreover, if the proportion of the wax-deficient area on the surface of the film is too high, the desired lubrication effect cannot be obtained in the wax-deficient area during press forming, and thus the friction coefficient becomes higher. Therefore, the area ratio of the wax-deficient area relative to the entire film is set to be 20.0% or less, preferably 15.0% or less, and more preferably 10.0% or less. On the other hand, the lower the area ratio, the higher the press forming property, so the lower limit is not particularly limited and can be 0%.

[0086] Average area of ​​wax deficiency: 50.0 μm 2 the following

[0087] As described above, by reducing the area ratio of the wax-deficient portion, the press moldability is improved. However, the research results of the present inventors show that even if the area ratio of the wax-deficient portion is 20.0% or less, when the average area of ​​the wax-deficient portion exceeds 50.0 μm 2 The desired press formability cannot be obtained. The reason is considered to be as follows.

[0088] That is, even if the total area ratio of the wax-deficient parts is the same, the actual distribution of the wax on the film surface is not necessarily the same. For example, sometimes, there are many small-sized wax-deficient parts scattered on the film surface, and sometimes, as a result of the condensation of the wax, although the number is small, there are large-sized wax-deficient parts on the film surface. Moreover, when the size of the wax-deficient parts is small, the adverse effect on the lubrication effect is relatively slight, but if the size of the wax-deficient parts is larger than a certain level, it will have a non-negligible effect on the lubrication effect. Therefore, in the present invention, the average area of ​​the wax-deficient parts is set to 50.0 μm 2 Below, preferably 20.0 μm 2 Below, more preferably 10.0 μm2 On the other hand, the smaller the average area, the better, so its lower limit is not particularly limited. However, from the viewpoint of industrial production, the average area of ​​the wax-deficient part may be 2.0 μm. 2 Above, 5.0 μm is also possible 2 above.

[0089] Therefore, by controlling the distribution of the wax so that both the area ratio of the wax-deficient portions and the average area of ​​the wax-deficient portions satisfy the above conditions, the press moldability can be extremely effectively improved.

[0090] Here, the wax-deficient portion is defined as a region in the film where the ratio of the mass of wax to the mass of organic resin is less than 1 / 10. In contrast, in regions other than the wax-deficient portion in the film, the ratio of the mass of wax to the mass of organic resin is higher than 1 / 10.

[0091] The average area and area ratio of the wax-deficient portion can be measured using microspectrophotometry, which can measure peaks belonging to the wax component and the organic resin component. Examples of the above-mentioned spectrophotometry include micro-Raman spectrophotometry and micro-FT-IR. The following describes a specific method for determining the average area and area ratio of the wax-deficient portion by spectrophotometry.

[0092] First, a mapping image of peak intensities corresponding to the wax component and the organic resin component is obtained by spectroscopy, and a mapping image of the peak intensity ratio of the wax component to the organic resin component is obtained by dividing the obtained peak intensity of the wax component by the peak intensity of the organic resin component.

[0093] Next, the peak intensity ratio mapping image is converted into a mapping image of the mass ratio of the wax component to the organic resin component. The conversion from the intensity ratio to the mass ratio can be performed using a calibration curve. The calibration curve is prepared in advance by measuring the mapping of the peak intensity ratio using a plurality of standard samples of a film having a known mass ratio of the wax component to the organic resin component.

[0094] Then, the area where the mass ratio of wax to organic resin is less than 1 / 10 is extracted as the wax-deficient part, and the area of ​​each independent wax-deficient part is calculated using image analysis software. The average value of the calculated areas of each independent wax-deficient part is calculated as the average area of ​​the wax-deficient part. In addition, the ratio of the total area of ​​each independent wax-deficient part to the area of ​​the measurement field of view is calculated as the area ratio of the wax-deficient part.

[0095] When determining the area ratio and average area of ​​the wax-deficient portion, the peaks measured may be the peaks belonging to the wax component and the organic resin component, but in order to reduce noise, it is preferred to use peaks with as high intensity as possible. For example, in micro-Raman spectroscopy, it is preferred to use the peak at 1295 cm corresponding to the bending vibration of CH2. -1 The peak at 1000 cm-1 corresponding to the stretching vibration of the aromatic ring chain is preferably used. -1 The peaks of are peaks attributed to styrene-based resins, epoxy-based resins, phenol-based resins, and polyester-based resins as organic resin components.

[0096] The measurement range of the peak intensity ratio mapping image must include a statistically significant number of wax-deficient parts, and is therefore preferably 80 μm×80 μm or more. The measurement range may be a continuous field of view or a combination of multiple fields of view.

[0097] As described above, the upper limit of the average particle size of the wax in the present invention is 3.0 μm. Therefore, from the viewpoint of determining the coagulation state of the wax, the interval between the measurement points of the mapping image is preferably 3 μm or less, more preferably 2 μm or less.

[0098] Figure 1 , 2 This is an example of a mapping image of the peak intensity ratio of the wax component to the organic resin component obtained by micro-Raman spectroscopy. The measurement range is 100 μm×100 μm, and the measurement conditions are as described above. Figure 1 is a mapping image of the peak intensity ratio of the film where the wax is more evenly distributed, and Figure 2 This is a mapping image of the peak intensity ratio of a film in which wax is unevenly distributed (a film in which wax is condensed).

[0099] Figure 3 , 4 It means separate analysis Figure 1 , 2 In the above analysis, first, a pre-made calibration curve is used to map the peak intensity ratio of the wax-deficient part. Figure 1 , 2 The peak intensity ratio mapping image shown in FIG. 1 was transformed into a mass ratio mapping image. Then, the wax deficiency area in the mass ratio mapping image was displayed as a white area using image analysis software. The area ratio and average area of ​​the wax deficiency area were respectively Figure 3 0.3% and 6.3μm 2 ,exist Figure 4 33.6% and 112.1μm 2 .

[0100] [Rust inhibitor]

[0101] The film does not rust under normal storage environment even when it does not contain a rust inhibitor. However, from the viewpoint of further improving the rust resistance, the film preferably further contains a rust inhibitor.

[0102] As the above-mentioned rust inhibitor, any rust inhibitor can be used without particular limitation, and preferably at least one selected from aluminum salts, zinc salts and zinc oxide of phosphoric acid is used. Here, phosphoric acid includes condensed phosphoric acids such as pyrophosphoric acid, tripolyphosphoric acid, tetrapolyphosphoric acid and metaphosphoric acid in addition to orthophosphoric acid. By using these rust inhibitors, a more excellent rust-proof effect can be exerted, and the deterioration of the coating stability is also small.

[0103] The content of the rust inhibitor is not particularly limited, but if the content of the rust inhibitor is too low, sometimes a sufficient effect cannot be obtained. In particular, when the coated steel sheets are stored in a coiled state, they are prone to rust due to moisture absorption. From the viewpoint of preventing rust even in such a harsh environment, it is preferred that the proportion of the rust inhibitor in the film is 5% or more. On the other hand, if the proportion of the rust inhibitor in the film exceeds 30%, sometimes the adhesion is deteriorated. In addition, sometimes the rust inhibitor precipitates in the state of the paint, and the paint stability is deteriorated. Therefore, it is preferred that the proportion of the rust inhibitor in the film is 30% or less.

[0104] Here, the ratio of the rust inhibitor in the film is defined as the ratio of the mass of the rust inhibitor in the film to the total mass of the total solid content in the film.

[0105] [Dispersant]

[0106] From the viewpoint of improving the dispersibility of the film components, the film preferably further contains a dispersant. As the dispersant, any dispersant can be used without particular limitation, and an anionic polymer dispersant is preferably used. In addition to being particularly effective in improving the dispersibility of particles of a few μm or less, anionic polymer dispersants can also be adsorbed on polyolefin wax. As the anionic polymer dispersant, at least one selected from sodium polycarboxylate, sodium polyacrylate, carboxylic acid copolymer and sulfonic acid copolymer is preferably used.

[0107] The proportion of the dispersant in the film is not particularly limited, but is preferably 0.5% or more. If the proportion of the dispersant in the film is 0.5% or more, the dispersibility of the wax in the coating is improved, and the uniformity of the wax distribution in the obtained film is improved. As a result, the desired wax distribution is easily achieved, and the compression moldability is further improved. On the other hand, if the proportion of the dispersant in the film exceeds 5%, the adhesiveness is sometimes deteriorated. Therefore, the proportion of the dispersant in the film is preferably 5% or less.

[0108] Here, the ratio of the dispersant in the film refers to the ratio of the mass of the dispersant in the film to the total mass of the solid content of all components in the film.

[0109] (Silicon Dioxide)

[0110] From the viewpoint of improving the water resistance and rust resistance of the film, it is preferred that the film further contains silicon dioxide. In addition, by containing silicon dioxide, the precipitation of the rust inhibitor contained in the coating can be suppressed, thereby improving the coating stability.

[0111] As the above-mentioned silica, any silica can be used without particular limitation. As the above-mentioned silica, colloidal silica is preferably used. The average particle size of the above-mentioned colloidal silica is not particularly limited, and is preferably above 5 nm. In addition, the average particle size of the above-mentioned colloidal silica is preferably below 200 nm. The average particle size of the above-mentioned colloidal silica can be measured by a dynamic light scattering method. Specifically, first, the particle size distribution under the scattering intensity standard is measured by a dynamic light scattering method. Then, the above-mentioned particle size distribution is converted from the scattering intensity standard to the volume standard. The median particle size D50 in the obtained volume-based particle size distribution is taken as the average particle size of the colloidal silica.

[0112] The proportion of silicon dioxide in the above-mentioned film is preferably 1% or more. By making the proportion of silicon dioxide in the film more than 1%, the waterproofness of the film is improved and the rust resistance is further improved. In addition, on the other hand, if the proportion of silicon dioxide in the film exceeds 10%, the adhesiveness sometimes deteriorates. Therefore, the proportion of silicon dioxide in the above-mentioned film is preferably less than 10%.

[0113] Here, the ratio of silicon dioxide in the film refers to the ratio of the mass of silicon dioxide in the film to the total mass of the solid content of all components in the film.

[0114] In addition, the ratio of each component contained in the said film can be calculated from the solid content mass of each film component at the time of coating preparation.

[0115] The film may contain other optional components in addition to the organic resin, wax, rust inhibitor, dispersant and silica. Examples of the other components include surface conditioners and defoamers that are usually added to paint.

[0116] Adhesion amount: 0.3g / m 2 above

[0117] When the coating weight is less than 0.3 g / m 2When the coating is applied to form the film, wax condensation easily occurs during the period from the coating is applied to the drying, so the desired wax distribution cannot be obtained, resulting in reduced press moldability. Therefore, the adhesion amount on one side of the film is 0.3 g / m 2 It should be noted that, as described later, the final wax distribution is affected by the surface roughness of the base steel plate. Therefore, from the viewpoint of being able to easily obtain the desired wax distribution even when the surface roughness of the base steel plate is large, it is preferred that the adhesion amount on one side of the film be 0.4 g / m 2 More preferably 0.6 g / m 2 More preferably, 0.8 g / m 2 On the other hand, the upper limit of the amount of the coating is not particularly limited, but if it exceeds 2.5 g / m 2 Therefore, the adhesion amount on one side of the film is preferably 2.5 g / m 2 the following.

[0118] The amount of film attached can be obtained by removing the film from the coated steel plate and dividing the mass difference before and after the film is removed by the area of ​​the steel plate. The film can be removed by any method as long as it is a method that can remove only the film without damaging the base steel plate. Typically, a solvent (organic solvent, etc.) that can dissolve the organic resin constituting the film, a stripping agent containing the above solvent, etc. can be used. When the above film is alkali-soluble, as described in the examples, it is preferred to use an alkali degreasing agent.

[0119] [Base steel plate]

[0120] As described above, in the present invention, excellent press formability is achieved by controlling the composition of the film and the distribution of the wax in the film. Therefore, any steel plate can be used as the base steel plate without particular limitation. The base steel plate can be a cold-rolled steel plate or a hot-rolled steel plate.

[0121] The tensile strength TS of the above-mentioned base steel plate is not particularly limited, but if it is too low, the strength of the finally obtained press-formed part is sometimes insufficient. Therefore, the tensile strength of the above-mentioned base steel plate is preferably above 260MPa. On the other hand, the upper limit of the above-mentioned tensile strength is not particularly limited. For example, when a high-strength steel plate with a tensile strength of more than 440MPa is used as the base steel plate, the surface pressure during press forming becomes high. However, according to the present invention, the friction coefficient between the steel plate and the mold can be significantly reduced, so even under such high surface pressure conditions, the generation of cracks and mold wear can be suppressed, and good press formability can be obtained. Therefore, the tensile strength of the base steel plate can be more than 440MPa. However, if the tensile strength is too high, it is difficult to press form into a complex shape. Therefore, from the viewpoint of press formability to complex shapes, the tensile strength of the above-mentioned base steel plate is preferably below 440MPa.

[0122] The thickness of the base steel plate is not particularly limited, but if it is too thin, the strength of the final press-formed part may be insufficient. Therefore, the thickness of the base steel plate is preferably 0.5 mm or more. On the other hand, the upper limit of the thickness is not particularly limited, but if it is too thick, it is difficult to press-form into a complex shape. Therefore, the thickness of the base steel plate is preferably 4.0 mm or less.

[0123] The surface roughness of the above-mentioned base steel plate (the surface roughness of the base steel plate before the film is formed) is not particularly limited. However, when the arithmetic mean roughness Ra of the base steel plate surface is greater than 2.5μm, the surface of the base steel plate is large, so the film formed in the concave portion is difficult to contact the mold during press forming. In addition, in the convex portion, the amount of film attached is less than that in the concave portion, so it is difficult to obtain the desired wax distribution, and as a result, the effect of improving the press formability is sometimes reduced. Therefore, from the viewpoint of further improving the press formability, it is preferred to make Ra less than 2.5μm. On the other hand, when Ra is less than 0.4μm, fine scratches that may be generated during press forming are easily conspicuous. In addition, if Ra is less than 0.4μm, wear sometimes occurs during press forming. Therefore, Ra is preferably above 0.4μm.

[0124] Here, the arithmetic mean roughness Ra of the base steel plate can be measured in accordance with JIS B 0633: 2001 (ISO 4288: 1996). For example, when Ra is greater than 0.1 and less than 2, the cutoff value and the reference length are set to 0.8 mm, the evaluation length is set to 4 mm, and Ra is obtained from the measured roughness curve. When Ra is greater than 2 and less than 10, the cutoff value and the reference length are set to 2.5 mm, the evaluation length is set to 12.5 mm, and Ra is obtained from the measured roughness curve.

[0125] (2) Manufacturing method

[0126] Next, the manufacturing method of the coated steel sheet of the present invention is described. In one embodiment of the present invention, the coated steel sheet is manufactured by applying a coating containing an organic resin and a wax to at least one surface of a base steel sheet and drying it. It should be noted that the points not specifically mentioned may be the same as the description of the coated steel sheet.

[0127] As the coating, for example, a coating obtained by adding wax to an organic resin solution in which an organic resin is dissolved in a solvent or an organic resin emulsion in which an organic resin is dispersed in a solvent can be used. As the solvent, one or both of water and an organic solvent can be used, but water is preferably used.

[0128] The ratio of the total solid content in the coating is not particularly limited, but is preferably 1 to 30%. When the ratio of the total solid content in the coating is less than 1% or exceeds 30%, uneven coating may occur, and the desired wax distribution may not be obtained. It should be noted that the ratio of the total solid content in the coating here refers to the concentration of the total solid content in the coating, that is, the ratio of the solid content mass to the total mass of the coating (including the solvent).

[0129] The coating on the base steel sheet can be applied by any method without particular limitation. Examples of the above-mentioned coating include methods using a roll coater, a rod coater, spraying, dipping, brushing, and the like. In the above-mentioned coating, in the finally obtained coated steel sheet, the coating adhesion amount on one side of the steel sheet is 0.3 g / m2 in terms of dry mass. 2 The coating material is applied in the above manner.

[0130] Drying after coating is applied may be performed by any method without particular limitation. Examples of the drying method include drying with hot air, drying with an IH heater, and a method using infrared heating.

[0131] The maximum temperature of the steel plate during drying is preferably 60°C to the melting point of the wax used. If the maximum temperature is less than 60°C, drying takes time and the rust resistance may be poor. On the other hand, when the maximum temperature exceeds the melting point of the wax, the wax melts and coalesces, and the particle size becomes coarse, making it difficult to obtain the desired wax distribution.

[0132] Example

[0133] Hereinafter, the present invention will be described by way of examples. However, it should be noted that the present invention is not limited to the following examples.

[0134] A coated steel sheet is produced by forming a coating on the surface of a base steel sheet in the following steps.

[0135] First, four types of base steel plates having arithmetic mean roughness Ra shown in Table 1 were prepared. Base steel plates A to C were cold-rolled steel plates with a plate thickness of 0.8 mm, and base steel plate D was a hot-rolled steel plate with a plate thickness of 2.0 mm. It should be noted that base steel plates A to D were all SPCD (JIS G 3141) and SPHD (JIS G 3131) having a tensile strength of 270 MPa.

[0136] In addition, coatings of the compositions shown in Tables 2 and 3 were prepared. The ratio of each component in Tables 2 and 3 is the ratio of the mass of the solid content of each component contained in the coating to the total mass of the total solid content. It should be noted that colloidal silica with a volume average particle size of 9 nm was used as silica. In addition, the molecular weight of the organic resin shown in Tables 2 and 3 and the melting point and average particle size of the wax are values ​​measured by the above method, respectively.

[0137] The coating was applied to the surface of the base steel plate using a bar coater, and heated and dried using an IH heater so that the maximum temperature of the steel plate surface reached 80°C to obtain a coated steel plate. The combinations of the base steel plate and the coating used are shown in Tables 4 to 7. It should be noted that, for comparison, in some comparative examples, the coating was not formed, and the base steel plate was directly used for the evaluation described below.

[0138] (Film adhesion amount)

[0139] The amount of film adhesion in the obtained coated steel plate is measured. Specifically, the film is removed from the coated steel plate, and the mass difference before and after the film removal is divided by the area of ​​the steel plate to calculate the adhesion amount. The removal of the above-mentioned film is carried out by immersing the coated steel plate in a degreasing solution with a degreasing agent concentration of 20 g / L and a temperature of 40°C for 300 seconds. As the above-mentioned degreasing agent, FINE CLEANER E6403 (manufactured by Nihon Parkerizing Co., Ltd.), an alkaline degreasing agent, is used. It should be noted that the film is completely removed under the above-mentioned conditions by the same method as the film removability test described later. The film adhesion amounts shown in Tables 4 to 7 are the values ​​on a single side of the steel plate.

[0140] (Wax lacking part)

[0141] Next, the area ratio and average area of ​​the wax-deficient portion on the film surface of the obtained coated steel sheet were evaluated in the following procedure.

[0142] First, five test pieces of 10 mm × 10 mm in size were cut from each of the coated steel sheets. A micro Raman device (LabRAM HR Evolution manufactured by Horiba Ltd.) was used to measure the vicinity of the center of the test piece to obtain a mapping image of the peak intensity corresponding to the wax component and the organic resin component. The measurement range was 100 μm × 100 μm, and the measurement interval was 1 μm. In addition, a 1295 cm -1 The peak at 1000 cm -1 The peak of is taken as the peak of the organic resin component.

[0143] Next, a mapping image of the peak intensity ratio of the wax component to the organic resin component is prepared by dividing the peak intensity of the wax component in the obtained mapping image by the peak intensity of the organic resin component. Then, the mapping image of the peak intensity ratio is converted into a mapping image of the mass ratio of the wax component to the organic resin component using a pre-prepared calibration curve.

[0144] In the obtained mass ratio mapping image, the measurement points where the mass ratio of wax to organic resin was 1 / 10 or less were determined as wax-deficient areas, and the area ratio and average area of ​​the wax-deficient areas were calculated. 2 The following wax-deficient portions are not treated as wax-deficient portions and are excluded from the calculation of the above-mentioned area ratio and average area.

[0145] The above measurement was performed on 5 test pieces, and the obtained area ratio and average area and the respective average values ​​were adopted as the area ratio and average area of ​​the wax-deficient portion. The obtained results are shown in Tables 4 to 7.

[0146] Next, the properties of the obtained coated steel sheets were evaluated according to the following procedures.

[0147] (Pressing Formability)

[0148] Press formability is related to sliding property, that is, the friction coefficient of the steel sheet surface. The lower the friction coefficient, the better the press formability. Therefore, in order to evaluate press formability, the friction coefficient of the obtained coated steel sheet was measured according to the following steps.

[0149] Figure 5: is a schematic front view showing a friction coefficient measuring device. As shown in the figure, a friction coefficient measuring sample 1 taken from a coated steel plate is fixed to a sample stand 2, and the sample stand 2 is fixed to the upper surface of a horizontally movable slide table 3. A slide table support 5 having a roller 4 connected thereto and movable up and down is provided on the lower surface of the slide table 3, and a first load cell 7 is mounted on the slide table support 5. The first load cell 7 is used to measure the push load N on the friction coefficient measuring sample 1 generated by the flange 6 by pushing the slide table support 5 upward. A second load cell 8 is mounted on one end of the slide table 3. The second load cell 8 is used to measure the sliding resistance F when the slide table 3 is moved in the horizontal direction under the condition that the above-mentioned push force is applied. It should be noted that the test was conducted by applying PRETON R352L, a cleaning oil for pressing manufactured by SUGIMURA Chemical Industrial Co., Ltd., to the surface of the sample 1 as a lubricating oil.

[0150] Figure 6 1 is a schematic perspective view showing the shape and size of the flange used. The lower surface of the flange 6 slides while being pressed against the surface of the sample 1 . Figure 6 The shape of the flange 6 shown is 10 mm wide and 59 mm long in the sliding direction of the sample. The lower parts of both ends in the sliding direction are composed of curved surfaces with a curvature of 4.5 mmR. The lower surface of the flange that pushes the sample has a flat surface with a width of 10 mm and a length of 50 mm in the sliding direction.

[0151] Friction coefficient test Figure 6 The flange shown was tested at a push load of 400 kgf and a sample pulling speed (horizontal moving speed of the slide table 3) of 20 cm / min. The friction coefficient μ between the sample and the flange was calculated by the formula: μ=F / N.

[0152] The obtained friction coefficient values ​​are shown in Tables 4 to 7. When the friction coefficient was 0.115 or less, the press moldability (sliding property) was judged to be good.

[0153] (Weldability)

[0154] When the press-formed parts obtained by press-forming the coated steel sheet are used for automobile bodies, etc., welding is usually performed in the assembly process. Therefore, the coated steel sheet is expected to have excellent weldability in addition to press-formability. Therefore, the weldability of the coated steel sheet is evaluated. Specifically, a continuous spot welding test is performed on the coated steel sheet under the conditions of using electrode: DR type Cr-Cu electrode, pressure: 150kgf, power-on time: 10 cycles / 60Hz, welding current: 7.5kA, and the number of continuous spots is calculated. When the number of continuous spots is 5000 or more, the weldability is evaluated as "good", and when it is less than 5000 points, the weldability is evaluated as "inadequate".

[0155] (Releasability)

[0156] Assuming that the coated steel sheet of the present invention is used for automobile applications, the removability during degreasing was evaluated. In order to determine the removability of the coating, each coated steel sheet was first immersed in a degreasing liquid having a degreasing agent concentration of 20 g / L and a temperature of 40° C. for a predetermined period of time, and then washed with tap water to perform degreasing. As the degreasing agent, FINECLEANER E6403 (manufactured by Nihon Parkerizing Co., Ltd.), which is an alkaline degreasing agent, was used.

[0157] Next, the surface carbon intensity of the degreased test piece was measured using a fluorescent X-ray analyzer. The film peeling rate was calculated using the following formula using the measured surface carbon intensity, the previously measured surface carbon intensity before degreasing, and the surface carbon intensity of the base steel plate.

[0158] Film peeling rate (%) = [(surface carbon strength before degreasing - surface carbon strength after degreasing) / (surface carbon strength before degreasing - surface carbon strength of base steel plate)] × 100

[0159] It should be noted that the surface carbon strength of the base steel plate herein refers to the surface carbon strength of the base steel plate before the film is formed.

[0160] The above test was conducted by changing the immersion time in the degreasing solution to obtain the immersion time in the alkaline degreasing solution at which the film peeling rate was 98% or more. The obtained immersion time was shown as "film stripping time" in Tables 4 to 7. When the above film stripping time was 120 seconds or less, it was judged to be good film stripping property.

[0161] (Rust resistance)

[0162] Assuming that the coated steel sheet is stored in a coiled state, the rust resistance in the overlapped state was evaluated. Specifically, a test piece of 150 mm × 70 mm in size was taken from the coated steel sheet, and the surface of the test piece was coated with 1.0 g / m 2 Then, the two test pieces were overlapped and the surface pressure was 0.02 kgf / mm. 2 The load was applied and the samples were kept in an environment of 50°C and 95%RH.

[0163] The inner side of the overlapped surface was checked every 7 days, and the number of days until rusting was evaluated. The case where the number of days until rusting was 56 days or more was evaluated as "excellent", the case where it was 21 days or more was evaluated as "good", and the case where it was less than 21 days was evaluated as "acceptable".

[0164] (Adhesion)

[0165] When the press-formed parts obtained by press-forming the coated steel sheet are used for automobile bodies, etc., bonding is sometimes performed during the assembly process. Therefore, the coated steel sheet is expected to have excellent adhesion in addition to press-formability. Therefore, the adhesion of the coated steel sheet is evaluated. Specifically, two test pieces of 100×25.4 mm in size are taken from each coated steel sheet and immersed in rust-proof oil. After the above-mentioned test piece is pulled up from the rust-proof oil, it is vertically stood for 24 hours to remove excess oil.

[0166] Next, an epoxy adhesive was uniformly applied to the surface of the test piece in an area of ​​25.4 mm × 13 mm with a thickness of 0.2 mm. Then, two test pieces were overlapped and clamped with a clip, and baked at 180°C for 20 minutes to dry and cure. After cooling, a shear tensile test was performed using an AUTOGRAPH testing machine to measure the shear adhesion. When the shear adhesion was 20 MPa or more, it was rated as good adhesion.

[0167] From the results shown in Tables 4 to 7, it can be seen that the friction coefficients of the coated steel sheets satisfying the conditions of the present invention are all below 0.115, and they have excellent press formability. In contrast, the friction coefficients of the coated steel sheets not satisfying the conditions of the present invention are all above 0.115, and they have poor press formability.

[0168] As described above, the coated steel sheet of the present invention is excellent in sliding property (press formability) during press forming and can be suitably used for various applications including automobile body applications.

[0169] Table 1

[0170] Steel Plate Ra(μm) A 0.48 B 0.78 C 1.48 D 2.35

[0171]

[0172]

[0173]

[0174]

[0175]

[0176]

[0177] Explanation of symbols

[0178] 1. Specimen for determination of friction coefficient

[0179] 2 Sample table

[0180] 3 Sliding table

[0181] 4 Rollers

[0182] 5 Sliding table support

[0183] 6 Flange

[0184] 7 First load cell

[0185] 8 Second load cell

[0186] 9 Guide Rail

Claims

1. A coated steel sheet comprising a base steel sheet and a coating film containing an organic resin and a wax provided on at least one surface of the base steel sheet, wherein: The organic resin is at least one selected from styrene resin, epoxy resin, phenolic resin and polyester resin. The wax is a polyolefin wax having a melting point of 100° C. to 145° C. and an average particle size of 3.0 μm or less. In the film, the area ratio of the wax-deficient portion to the entire film is 20.0% or less, and the wax-deficient portion is defined as a region where the ratio of the mass of the wax to the mass of the organic resin is 1 / 10 or less, The average area of ​​the wax-deficient part was 50.0 μm 2 the following, The adhesion amount on one side of the film is 0.3 g / m 2 above.

2. The coated steel sheet according to claim 1, wherein: The ratio of the organic resin in the film is 30% by mass to 95% by mass. The ratio of the wax in the film is 5% by mass to 50% by mass.

3. The coated steel sheet according to claim 1 or 2, wherein: The arithmetic mean roughness Ra of the surface of the base steel plate is 0.4 μm to 2.5 μm.

4. The coated steel sheet according to any one of claims 1 to 3, wherein The adhesion amount on one side of the film is 2.5 g / m 2 the following.

5. The coated steel sheet according to any one of claims 1 to 4, wherein The organic resin is an alkali-soluble resin.

6. The coated steel sheet according to any one of claims 1 to 5, wherein The film further contains a rust inhibitor.

7. The coated steel sheet according to claim 6, wherein: The rust inhibitor is at least one selected from aluminum salts, zinc salts and zinc oxide of phosphoric acid.

8. The coated steel sheet according to any one of claims 1 to 7, wherein The film further contains a dispersant.

9. The coated steel sheet according to claim 8, wherein: The dispersant is at least one selected from sodium polycarboxylate, sodium polyacrylate, carboxylic acid copolymer and sulfonic acid copolymer.

10. The coated steel sheet according to any one of claims 1 to 9, wherein The film further contains silicon dioxide.

11. A method for producing a coated steel sheet according to any one of claims 1 to 10, comprising applying a coating comprising an organic resin and a wax to at least one surface of a base steel sheet and drying the coating, wherein: The organic resin is at least one selected from styrene resin, epoxy resin, phenolic resin and polyester resin. The wax is a polyolefin wax having a melting point of 100° C. to 145° C. and an average particle size of 3.0 μm or less.

12. The method for producing a coated steel sheet according to claim 11, wherein: The maximum reaching temperature of the base steel sheet during the drying is 60° C. or higher and equal to or lower than the melting point of the wax.

13. The method for producing a coated steel sheet according to claim 11 or 12, wherein: The ratio of the total solid content in the coating material is 1% by mass to 30% by mass.

Citation Information

Patent Citations

  • Steel sheet and method for manufacturing same

    CN118056034A

  • Lubricating film-coated zinc-plated steel sheet and method for producing same

    CN118475722A

  • Resin-coated metal sheet and resin composition

    CN1907579A

  • Lubricative stainless steel sheets and pipes and method of producing them

    EP1099485A2

  • Lubricating resin-treated steel sheet excellent in press forming property and corrosion resistance

    JP1995041962A